2011
DOI: 10.1603/me10178
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field-Based Tests of Deltamethrin Insecticides Against Adult Culicoides Biting Midges

Abstract: Bluetongue virus (BTV) is an economically important arbovirus of ruminants transmitted by Culicoides biting midges. Vector control using residual spraying or application to livestock is recommended by many authorities to reduce BTV transmission; however, the impact of these measures in terms of both inflicting mortality on Culicoides and subsequently upon BTV transmission is unclear. This study consisted of a standardized World Health Organization laboratory assay to determine the susceptibility of European Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 21 publications
1
48
2
Order By: Relevance
“…Treatment caused mortality to midges for 35 days or more, but mortality never reached 100%. Venail et al (2011) showed that Culicoides spp. were quite susceptible to deltamethrin in the lab.…”
Section: Recent Studies On Insecticides For Prevention Of Feeding By mentioning
confidence: 99%
“…Treatment caused mortality to midges for 35 days or more, but mortality never reached 100%. Venail et al (2011) showed that Culicoides spp. were quite susceptible to deltamethrin in the lab.…”
Section: Recent Studies On Insecticides For Prevention Of Feeding By mentioning
confidence: 99%
“…Insecticides applied to host animals have shown some potential for causing high mortality in host-seeking females. A recent study determined the susceptibility of European Culicoides species to deltamethrin in a field trial consisting of a pour-on formulation of the insecticide applied to sheep [18]. They found a maximum mortality rate of 49% at 4 days post-application, and duration of lethal effect was predicted to be as short as 10 days, with susceptibility differences for the different Culicoides species.…”
Section: Introductionmentioning
confidence: 99%
“…permethrin (Stevens et al, 1988;Mullens et al, 2000), fenvalerate pyrethroid (Holbrook, 1986), cypermethrin (Papadopoulus, 2010) and alphacypermethrin (Papadopoulos et al, 2009), have shown significant negative effects on colonyreared Culicoides (Monoculicoides) sonorensis Wirth and Jones and Culicoides (Monoculicoides) nubeculosis Meigen. Susceptibility to deltamethrin was found to be higher in colony reared C. nubeculosus, than in field populations of Culicoides (Avaritia) obsoletus Meigen or Culicoides (Avaritia) imicola Kieffer (Venail et al, 2011). In bioassay determinations of the efficacy of permethrins against C. sonorensis it was shown that midges 3 were able to feed, and thus potentially transmit pathogens, before being incapacitated (Mullens et al, 2000).…”
Section: Introductionmentioning
confidence: 99%